1991
DOI: 10.1111/j.1525-1314.1991.tb00560.x
|View full text |Cite
|
Sign up to set email alerts
|

Compositional variations in mafic phyllosilicates from regional low‐grade metabasites and application of the chlorite geothermometer

Abstract: Mafic phyllosilicates in metabasites affected by low-grade regional metamorphism from Wales and eastern North Greenland show variations in their structure and chemistry. These variations are related to four mineral zones in these metabasites, which are recognized on the presence/absence of various key calc-silicate minerals and also actinolite. Zones 1 and 2 equate with the zeolite facies, zone 3 with the prehnite-pumpellyite facies (or prehnite-actinolite facies in rocks with appropriate bulk rock composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(53 citation statements)
references
References 24 publications
4
49
0
Order By: Relevance
“…If this method and the resulting empirical calibration are used to determine temperatures in chlorites from similar settings (bulk rock composition, f02, etc. ), satisfactory results may be obtained (Bevins et al, 1991). This empirical approach has two important advantages: 1) It takes into account, although not explicitly, the compositional effects of a multitude of thermodynamic variables that do not need to be measured, assuming one can be satisfied that physicochemical conditions of chlorite growth are/were similar to those where the calibration was undertaken; and 2) it is simple to apply, since it generally has the form of a linear function.…”
Section: Discussion: Comparison Of Chlorite Geothermometersmentioning
confidence: 99%
See 2 more Smart Citations
“…If this method and the resulting empirical calibration are used to determine temperatures in chlorites from similar settings (bulk rock composition, f02, etc. ), satisfactory results may be obtained (Bevins et al, 1991). This empirical approach has two important advantages: 1) It takes into account, although not explicitly, the compositional effects of a multitude of thermodynamic variables that do not need to be measured, assuming one can be satisfied that physicochemical conditions of chlorite growth are/were similar to those where the calibration was undertaken; and 2) it is simple to apply, since it generally has the form of a linear function.…”
Section: Discussion: Comparison Of Chlorite Geothermometersmentioning
confidence: 99%
“…In chlorites, it has been shown that the Fe/(Fe + Mg) ratios of chlorite and bulk host rock are directly proportional to each other (Cathelineau and Nieva, 1985, Figure 6;Bevins et al, 1991, Figure 2), indicating at least some bulk rock compositional control. As is the case for biotite, it is likely that bulk rock mineralogy or composition will exercise some control over the composition of chlorite.…”
Section: Description Of Chlorite Non-stoichiometry and Calculation Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…The gradual or continuous transformation of smectite to chlorite, as accommodated through randomly interlayered S/C (with various percentages of expandable layers) and regularly interlayered C/S (corrensite), has been reported from metabasalts (Bettison and Schiffman 1988;Bevins et al 1991) and sediments (Helmhold and van der Kamp 1984;Chang et al 1986). However, a discontinuous decrease in smectite proportion, whereby smectite (with less than 20% chlorite), corrensite and chlorite (with less than 10% smectite) occur with increasing temperature, has been reported from diagenetic and hydrothermal environments (Inoue et al 1984;Inoue 1987;Inoue and Utada 1991;Schiffman and Staudigel 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Among several potential chlorite geothermometers, that using the tetrahedral Al content of trioctahedral chlorite has been increasingly used in low-grade regimes in recent years (Cathelineau 1988;Bevins et al 1991). However, chemical analysis of phyllosilicates in low-grade rocks is fraught with difficulty because of the small grain sizes, mixed layering, and complex intergrowths that exist at scales beyond the resolution limits of the electron microprobe and conventional analytical techniques (Peacor 1992;Warren and Ransom 1992).…”
Section: Introductionmentioning
confidence: 99%